2015
DOI: 10.1007/s11692-015-9333-8
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Fluctuating Selection on Morphological and Reproductive Traits in Female Tree Swallow (Tachycineta bicolor)

Abstract: Temporally replicated studies are essential to describe and understand selection in natural populations. Selection patterns can differ among life stages representing different fitness components. Despite the increasing number of long-term studies, yearly estimates of fluctuation in strength and direction are mostly available from studies conducted on a limited number of years. Based on a population of Tree swallows (Tachycineta bicolor) monitored over 10,200 km 2 in Southern Québec, Canada, since 2004, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 55 publications
2
24
0
1
Order By: Relevance
“…A previous analysis in our study system showed that selection favoured earlier laying date in this population but that patterns of selection fluctuated in strength and direction through time (Millet et al. ). Also, the time lag observed in the studied area between spring arrival (eBird, http://ebird.org/) and reproduction suggests that further adjustments of laying date are possible.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…A previous analysis in our study system showed that selection favoured earlier laying date in this population but that patterns of selection fluctuated in strength and direction through time (Millet et al. ). Also, the time lag observed in the studied area between spring arrival (eBird, http://ebird.org/) and reproduction suggests that further adjustments of laying date are possible.…”
Section: Introductionmentioning
confidence: 53%
“…While we believe that the pattern described here is likely to be nonadaptive, given that tree swallows breeding later show a reduced fitness in most years (Millet et al. ), further investigations are needed to clearly conclude on the effects of reduced plasticity in lower density habitats (e.g. compare selection gradients between low and high breeder density farms).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In our system, environmental conditions vary greatly within and between reproductive seasons and can have a large impact on within-year reproductive success of tree swallows (Lessard et al 2014, Rioux Paquette et al 2014, Bourret et al 2015, Millet et al 2015. Indeed, a post hoc analysis showed that there is no temporal autocorrelation (Appendix S1: Figs.…”
Section: Discussionmentioning
confidence: 93%
“…For instance, the positive relationship between female mass and reproductive success could suggest that females with greater energy supplies consistently produce more fledglings, as female mass positively affects clutch size and fledging success (see Fig. 2A; Winkler and Allen 1995, Rioux Paquette et al 2014, Millet et al 2015, Pellerin et al 2016. Our repeatability analyses controlled for female mass, but several other factors linked to female identity could influence Notes: CI, confidence interval.…”
Section: Discussionmentioning
confidence: 99%